2022
DOI: 10.1093/bioinformatics/btac616
|View full text |Cite
|
Sign up to set email alerts
|

dsMTL: a computational framework for privacy-preserving, distributed multi-task machine learning

Abstract: Motivation In multi-cohort machine learning studies, it is critical to differentiate between effects that are reproducible across cohorts and those that are cohort-specific. Multi-task learning (MTL) is a machine learning approach that facilitates this differentiation through the simultaneous learning of prediction tasks across cohorts. Since multi-cohort data can often not be combined into a single storage solution, there would be the substantial utility of an MTL application for geographica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…And the underlying true model is expected to be identified by considering the task-specific variations. This method has been used for the integration of multi-cohort gene expression datasets to identify expression signatures in brain samples from donors with schizophrenia (27). This study illustrated that MTL models showed higher reproducibility to unseen data cohorts than conventional machine learning methods and may thus be of particular use for the identification of reproducible biomarker signatures across studies.…”
Section: Multi-task Learning Incorporating Pairwise Task Similaritymentioning
confidence: 99%
See 4 more Smart Citations
“…And the underlying true model is expected to be identified by considering the task-specific variations. This method has been used for the integration of multi-cohort gene expression datasets to identify expression signatures in brain samples from donors with schizophrenia (27). This study illustrated that MTL models showed higher reproducibility to unseen data cohorts than conventional machine learning methods and may thus be of particular use for the identification of reproducible biomarker signatures across studies.…”
Section: Multi-task Learning Incorporating Pairwise Task Similaritymentioning
confidence: 99%
“…This review aims to highlight MTL's utility for multi-modal data analysis. In biomedical applications, it is common to analyze the integration of heterogeneous but related data modalities, e.g., predictions at different time points during illness progression (26), case-control classification in different cohorts (27), or response prediction of multiple drugs (12). In psychiatric research, MTL has already been used to integrate schizophrenia markers from multiple cohorts (27) as well as measures of cognitive functioning and structural neuroimaging (28).…”
Section: Multi-task Learning For Multi-modal Data Analysis In Neuroge...mentioning
confidence: 99%
See 3 more Smart Citations